High-field magnetization and electronic spin resonance study in the twisted honeycomb lattice α-Mn2V2O7. (16th March 2023) - Chen, R; Hu, H J; Qu, Z; Song, Y R; Lei, Q K; Liu, C B; Tang, Y S; Wang, C L; He, Z Z; Ouyang, Z W; Zhang, K; Qiu, Y; et al.
Abstract: We report the single-crystal growth of Mn2 V2 O7 and the results of magnetic susceptibility, high-field magnetization up to 55 T and high-frequency electric spin resonance (ESR) measurements for its low-temperature α phase. Two antiferromagnetic (AFM) ordering at 17.5 K and 3 K and obvious magnetic anisotropy are observed in α -Mn2 V2 O7 upon cooling. In pulsed high magnetic fields, the compound reaches the saturation magnetic moment of ∼10.5 μ B for each molecular formula at around 45 T after two undergoing AFM phase transitions at H c1 ≈ 16 T, H c2 ≈ 34.5 T for H //[ 1 1 ˉ 0 ] and H sf1 = 2.5 T, H sf2 = 7 T for H //[ 001 ]. In these two directions, two and seven resonance modes are detected by ESR spectroscopy, respectively. The ω 1 and ω 2 modes of H //[ 1 1 ˉ 0 ] can be well described by two-sublattice AFM resonance mode with two zero-field gaps at 94.51 GHz and 169.28 GHz, indicating a hard-axis feature. The seven modes for H //[ 001 ] are partially separated by the critical fields of H sf1 and H sf2, displaying the two signs of spin-flop transition. The fittings of ω c1 and ω c2 modes yield zero-field gaps at 69.50 GHz and 84.73 GHz for H //[ 001 ], confirming the axis-type anisotropy. The saturated moment and gyromagnetic ratio indicate the Mn 2+ ion in α -Mn2 V2 O7 is in a high spin state with orbital moment completely quenched. A quasi-one-dimensional magnetism with a zig-zag-chain spin configuration is suggested in α -Mn2 V2 O7, due to the special neighbor interactions caused by a distorted network structure with honeycomb layer.